The attitude of the People’s Republic of China towards the Arctic (Economic and Political Thought, 2015)
Transformations of the Arctic region cause serious implications for boththe Arctic countries and other participants of international relations. Forthe sake of geographical, economic and political conditions, China is one ofthe countries which pay special attention to monitoring the developmentsbeyond the Arctic Circle. This article examines aspects of Chinese interestin the region in terms of access to raw materials, the future opening ofArctic shipping routes and opportunities to realise research, while rising theproblem of the relations with the Arctic countries.